2017
DOI: 10.1111/anae.14065
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide‐based vs. nitrous oxide‐free general anaesthesia and accidental awareness in surgical patients: an abridged Cochrane systematic review

Abstract: Summary Accidental awareness during general anaesthesia can arise from a failure to deliver sufficient anaesthetic agent, or from a patient's resistance to an expected sufficient dose of such an agent. Awareness is ‘explicit’ if the patient is subsequently able to recall the event. We conducted a systematic review into the effect of nitrous oxide used as part of a general anaesthetic on the risk of accidental awareness in people over the age of five years undergoing general anaesthesia for surgery. We included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
(148 reference statements)
0
2
0
Order By: Relevance
“…For instance, the accidental awareness during general anesthesia determines the success or failure of the surgery. 24,25 Previous research has revealed that the emergence of unintended awareness during the procedure of laryngoscopy is 1/25, and the collection of spontaneously self-reported awareness intra-operative of patients by the Royal College of Anesthetist Nation Audit Project showed that the incidence of surgical responsiveness was up to 1/800 in the United States in 2018. 26,27 BIS, which was previously considered as the most accurate anesthesia monitoring strategy, has been suggested to be affected by the variations in analgesic agents and patients' age, causing several complications such as hypertension, hypotension, hypoxemia, and accidental awareness during the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the accidental awareness during general anesthesia determines the success or failure of the surgery. 24,25 Previous research has revealed that the emergence of unintended awareness during the procedure of laryngoscopy is 1/25, and the collection of spontaneously self-reported awareness intra-operative of patients by the Royal College of Anesthetist Nation Audit Project showed that the incidence of surgical responsiveness was up to 1/800 in the United States in 2018. 26,27 BIS, which was previously considered as the most accurate anesthesia monitoring strategy, has been suggested to be affected by the variations in analgesic agents and patients' age, causing several complications such as hypertension, hypotension, hypoxemia, and accidental awareness during the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For most anesthesiologists a frequent conversation that occurs prior to surgery is one in which the patient requests that he or she ''does not want to hear or feel anything'' during surgery. Awareness under GA occurs very rarely [26], though it does occur. The level of sedation administered during surgery performed with regional anesthesia as the primary technique is variable with some centers opting for light or no sedation and others administering moderate to deep sedation.…”
Section: General Anesthesia For Ambulatory Total Joint Arthroplastymentioning
confidence: 99%